Assessment of heavy metals contamination in sediments from three adjacent regions of the Yellow River using metal chemical fractions and multivariate analysis techniques. (February 2016) - Ma, Xiaoling; Zuo, Hang; Tian, Mengjing; Zhang, Liyang; Meng, Jia; Zhou, Xuening; Min, Na; Chang, Xinyuan; Liu, Ying
Abstract: Metal chemical fractions obtained by optimized BCR three-stage extraction procedure and multivariate analysis techniques were exploited for assessing 7 heavy metals (Cr, Pb, Cd, Co, Cu, Zn and Ni) in sediments from Gansu province, Ningxia and Inner Mongolia Autonomous Regions of the Yellow River in Northern China. The results indicated that higher susceptibility and bioavailability of Cr and Cd with a strong anthropogenic source were due to their higher availability in the exchangeable fraction. A portion of Pb, Cd, Co, Zn, and Ni in reducible fraction may be due to the fact that they can form stable complexes with Fe and Mn oxides. Substantial amount of Pb, Co, Ni and Cu was observed as oxidizable fraction because of their strong affinity to the organic matters so that they can complex with humic substances in sediments. The high geo-accumulation indexes ( I geo ) for Cr and Cd showed their higher environmental risk to the aquatic biota. Principal component analysis (PCA) revealed that high toxic Cr and Cd in polluted sites (Cd in S10, S11 and Cr in S13) may be contributed to anthropogenic sources, it was consistent with the results of dual hierarchical clustering analysis (DHCA), which could give more details about contributing sources. Highlights: The Inner Mongolia section of the Yellow River contains higher pollution degree of heavy metals in sediment samples. Cr and Cd are two non-negligible metals which may pose higher threat to aquatic biota. PCA reveals that the excess Cr and Cd in study regions mostly reflect the anthropogenic sources. The pollution of Co and Cd may be related to the socio-economic development according to DHCA.